Scrivere e risignificare. Tre percorsi dal dramma incompiuto Andrea e il Presidente a Foglio di via e altri versi di Franco Fortini - Romano, Jacopo Maria (L'ospite ingrato, 2024)
The article analyses Franco Fortini’s unfinished tragedy Andrea e il Presidente (circa 1943-1945) and traces its developmental trajectory through documents preserved in the Franco Fortini Archive. It shows how, despite being left incomplete by the author, the play maintains a complex relationship with his debut poetry collection Foglio di via e altri versi (1946), starting with the early versions of the poems Coro dell’ultimo atto, Sonetto, and Varsavia 1944. The study explores the evolution of these texts, from various drafts of the play to their inclusion in Foglio di via, focusing on formal changes, the implications of shifts in the subject of enunciation, and paratextual additions.